2020
DOI: 10.1159/000509610
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pulmonary Auscultation in Patients with 2019 Novel Coronavirus in China

Abstract: <b><i>Background:</i></b> Effective auscultations are often hard to implement in isolation wards. To date, little is known about the characteristics of pulmonary auscultation in novel coronavirus (COVID-19) pneumonia. <b><i>Objectives:</i></b> The aim of this study was to explore the features and clinical significance of pulmonary auscultation in COVID-19 pneumonia using an electronic stethoscope in isolation wards. <b><i>Methods:</i></b> … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Third, prolonged continuous monitoring of lung sound is almost impractical. Lastly, a practitioner wearing personal protective equipment finds it difficult to perform auscultation without breaching the protection [8], which limits the use of auscultation on a patient with an airborne or droplet-transmitted pulmonary disease, such as coronavirus disease 2019 (COVID-19) [9][10][11]. To overcome the aforementioned limitations, computerized respiratory sound analysis [12] is required.…”
Section: Introductionmentioning
confidence: 99%
“…Third, prolonged continuous monitoring of lung sound is almost impractical. Lastly, a practitioner wearing personal protective equipment finds it difficult to perform auscultation without breaching the protection [8], which limits the use of auscultation on a patient with an airborne or droplet-transmitted pulmonary disease, such as coronavirus disease 2019 (COVID-19) [9][10][11]. To overcome the aforementioned limitations, computerized respiratory sound analysis [12] is required.…”
Section: Introductionmentioning
confidence: 99%
“…2), an abnormal nature was usually observed by COVID-19 subjects, while healthy subjects had a more regular pattern during breathing. This could be related to the hidden characteristics of COVID-19 contaminated within lungs and exhibited during lung inhale and exhale [47][48][49]. Additionally, the MFCC transformation of these recordings (Fig.…”
Section: Smartphone-based Breathing Recordingsmentioning
confidence: 89%
“…Many studies have investigated the information carried by respiratory sounds in patients tested positive for COVID-19 [16][17][18]. Furthermore, it has been found that vocal patterns extracted from COVID-19 patients' speech recordings carry indicative biomarkers for the existence of the viral infection [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such findings are subject to observer variation however, and the absence of such signs does not denote absence of disease. 35 …”
Section: Methodsmentioning
confidence: 99%